1979
DOI: 10.1037/0022-3514.37.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous changes in heart rate on facilitation of thought and resistance to persuasion.

Abstract: Two experiments were conducted to examine the effects of an accelerated heart rate on information processing and resistance to persuasion. Experiment 1 addressed the effects on cognitive performance of manipulating heart rate exogenously for brief periods of time. Fourteen subjects wearing implanted demand-type cardiac pacemakers performed reading comprehension and sentence generation tasks while their heart rate was either accelerated or not accelerated. Results revealed that performance was better when heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…A similar effect was achieved by miming Salat, but it was not as great as actual Salat, and subjects performing actual Salat had a higher HR. This result is in agreement with the findings of Cacippo 39) .…”
Section: Discussionsupporting
confidence: 83%
“…A similar effect was achieved by miming Salat, but it was not as great as actual Salat, and subjects performing actual Salat had a higher HR. This result is in agreement with the findings of Cacippo 39) .…”
Section: Discussionsupporting
confidence: 83%
“…The results supported the hypothesis, showing that participants who were given caffeine were higher in physiological arousal (higher pulse rate) and showed greater agreement with the message than did those given a placebo. In agreement with this finding, two studies by Cacioppo, Sandman, and Walker (1978; see also Cacioppo, 1979) reported that an increased heart rate was associated with greater attitude change to a counterattitudinal message because the increased arousal induced greater cognitive elaborations.…”
mentioning
confidence: 53%
“…In a more definitive test of the hypothesis that transient and specific heart rate could affect message processing, Cacioppo (1979) conducted an additional persuasion study in a cardiology clinic using fully informed outpatients who had implanted cardiac pacemakers. The patients' pacemakers were "demand type," so called because they paced the heart at a constant rate (72 bpm) when natural pacing produced a rate below the set level.…”
Section: Message Modalitymentioning
confidence: 99%
“…External distraction (Petty, Wells, & Brock, 1976) Transient heart rate (Cacioppo, 1979) Recipient Posture (Petty, Wells, Heesacker, Brock, & Cacioppo, 1983) Need for cognition (Cacioppo, Moderate message repetition Petty, & Morris, 1983) Forewarning of message content (Petty & Cacioppo, 1977) Forewarning of persuasive intent (Petty & Cacioppo, 1979a) Excessive message repetition (Cacioppo & Petty, 1979b) Self-schemata (Cacioppo, Petty, & Sidera, 1982) Hemispheric asymmetry (Cacioppo, Petty, & Quintanar, 1982) Vertical/horizontal head movements (Wells & Petty, 1980) high in need for cognition may have the general goal of thinking, but may not exert the effort on a particular day due to mental fatigue. Little research has been directed explicitly at specifying what variables affect this stage, although effort has been linked previously to drive and arousal (e.g., Kahneman, 1973).…”
Section: Determinants Of Elaboration Likelihoodmentioning
confidence: 99%